Influence area as competitiveness' indicator for retail clusters (Gestão & Regionalidade, 2024)
Organizations are facing increasingly competitive environments and, in this sense, are adopting, among other strategies, more cooperative approaches based on collective operation perspectives. Commercial business concentrations offering related products to end consumers, treated in this paper as retail clusters, are a generally successful example of this stance type. In this context, this study aims to investigate this phenomenon, focusing on the ownership of the influence area concept as a consistent and relevant indicator in the assessment of the retail cluster's competitiveness. We have opted to investigate pub clusters for the field study. Based on the literature review, we sought to raise the theoretical foundation and empirical evidence to support the hypothesis of significant association between competitiveness and influence area for retail clusters. The results show consistent indications of the relationship between competitiveness and secondary and tertiary influence areas of retail clusters, offering an innovative contribution in the assessment of retail clusters' competitiveness, as well as the feasibility for using the influence area as a relevant marker to clusters management.
Keywords: Commercial concentrations; Retail Clusters; Business Network; Influence area; competitiveness